Using Health Information Resources for People With Cognitive Impairment (digiDEM Bayern): Registry-Based Cohort Study - Florian Weidinger; Nikolas Dietzel; Elmar Graessel; Hans-Ulrich Prokosch; Peter Kolominsky-Rabas (JMIR Formative Research)
Abstract BackgroundDementia is a growing global health challenge with significant economic and social implications. Underdiagnosis of dementia is prevalent due to a lack of knowledge and understanding among the general population. Enhancing dementia literacy through improved health information–seeking behavior is crucial for the self-determined management of the disease by those affected. Understanding the relationship between dementia literacy, health information–seeking behavior, and the use of various information sources among individuals with cognitive impairment is of high importance in this context. ObjectiveThe aim of this study was to analyze the relevance of different sources of health information from the perspective of people with cognitive impairment, while also evaluating differences based on age, gender, and disease progression. MethodsThis study is part of the ongoing project “Digital Dementia Registry Bavaria – digiDEM Bayern.” The Digital Dementia Registry Bavaria is a multicenter, prospective, longitudinal register study in Bavaria, Germany. People with cognitive impairment rated several information sources by using Likert scales with the values unimportant (1) to very important (5). Data were analyzed descriptively, and multiple 2-sample, 2-tailed t ResultsData of 924 people with cognitive impairment (531 with dementia, 393 with mild cognitive impairment) were evaluated. The most relevant health information sources were “Personal visit to a medical professional” (mean 3.9, SD 1.1) and “Family / Friends” (mean 3.9, SD 1.2). “Internet” was 1 of the 2 lowest-rated information sources by people with cognitive impairment (mean 1.6, SD 1.1), with nearly three-quarters (684/924, 74%) of the participants rating the source as unimportant. The age-specific analyses showed significant differences for the sources “Internet” (F2,921PF2,921PF2,921Pt640Pt685P ConclusionsTo enhance health and dementia literacy, the best way to communicate health information to people with cognitive impairment is through interpersonal contact with medical professionals and their friends and family. Slight changes in valuation should be considered as the medical condition progresses, along with variations by age and gender. In particular, the evaluation and use of the internet are dependent on these factors. Further research is needed to capture potential changes in the valuation of the internet as a health information source.